2020
DOI: 10.3390/land9030088
|View full text |Cite
|
Sign up to set email alerts
|

Migration, Remittances, and Forest Cover Change in Rural Guatemala and Chiapas, Mexico

Abstract: This article investigates how migration and remittances affect forest cover in eight rural communities in Guatemala and Chiapas, Mexico. Based on household surveys and remote sensing data, we found little evidence to support the widespread claim that migration takes pressure off forests. In the Chiapas sites, we observed no significant changes in forest cover since 1990, while in the Guatemalan sites, migration may have increased demand for agricultural land, leading to an average annual forest loss of 0.73% d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 60 publications
1
18
0
1
Order By: Relevance
“…These outbound flows of people eventually, when the migrants consolidate their socioeconomic position, translate into inbound flows of cash through migratory remittances (Courtney Smith 2006; Gomberg‐Muñoz 2011). The money sent back by the migrants to their relatives that remained in the village to help them or to improve the family’s standing by buying lands for housing or cultivation of more fields (Angelsen et al 2020). Although we do not have numbers for Santiago, the aggregates for the state of Oaxaca give an idea of importance of this phenomenon for the local economies.…”
Section: Modernity’s Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…These outbound flows of people eventually, when the migrants consolidate their socioeconomic position, translate into inbound flows of cash through migratory remittances (Courtney Smith 2006; Gomberg‐Muñoz 2011). The money sent back by the migrants to their relatives that remained in the village to help them or to improve the family’s standing by buying lands for housing or cultivation of more fields (Angelsen et al 2020). Although we do not have numbers for Santiago, the aggregates for the state of Oaxaca give an idea of importance of this phenomenon for the local economies.…”
Section: Modernity’s Flowsmentioning
confidence: 99%
“…The social production of the space (Lefebvre 1992) began to include factors beyond the traditional self‐subsisting agricultural village. Due to the considerable amounts of cash suddenly available to the families, some of them reduced or stopped altogether their cultivation efforts, food (traditional and non‐traditional) could be bought (Angelsen et al 2020). Contrasting with the traditional dwellings made of adobe or wood, some large houses of cement (status markers) were built and kept empty for most of the year or were taken care of by local family members on behalf of the “americanos” (used to refer to those migrating to the U.S.).…”
Section: Modernity’s Flowsmentioning
confidence: 99%
“…More evidence is needed on the implications of migration and remittances for forests and forestbased rural livelihoods which remain largely unexplored in the empirical literature (Hecht et al 2015). A few exceptions include Angelsen et al (2020) and López-Feldman and Chávez (2017). Based on household data from Guatemala and Mexico, Angelsen et al (2020) show that migration is not linked to expansion of agricultural land and only partially correlated with the use of chemical inputs, whereas the impact of remittances was not tested.…”
Section: Introductionmentioning
confidence: 98%
“…Other studies have shown that wildfires (Oliveira et al, 2017), farmers, and ethnic minorities with low education levels (Do & Mulia, 2018), a relaxed regulatory policy (Marcos‐Martinez et al, 2018), political transition (Biswas et al, 2021), and displaced deforestation (Pendrill et al, 2019) could impede or reverse forest transitions. The path to net forest gains is also dependent on agro‐ecological and climatic conditions as well as on population trends and urbanization (Nanni et al, 2019), livestock efficiency gains and woodfuel substitution (Gingrich et al, 2021), international outmigration and migrant remittances (Angelsen et al, 2020; Oldekop et al, 2018; Ospina et al, 2019), and climate (Harvey et al, 2020).…”
Section: Introductionmentioning
confidence: 99%